Design and Construction Application Electronic Learning of Sumbawa Language - Esabella, Shinta; Susilawati, Tri; Hidayatullah, Muhammad; Dery Sofya, Nora; Akhir Putra, Juniardi; Gunawan (Bulletin of Information Technology (BIT), 2024)
Preservation of Sumbawa Regional Language (Basa Samawa) through E-Learning Platform in Learning Innovation for Teenagers is an application that has been successfully created using the Rapid Application Development (RAD) software development method which includes the requirement planning phase, use design phase, construction phase, and cutover phase. The design model used in developing the application is the Data Flow Diagram (DFD). This application can be optimized for use by the Sumbawa Regency Education and Culture Office (DIKBUD), teachers, and students in the Sumbawa Regency area. The use of the application can be maximized by teenagers to learn the Sumbawa language according to the learning model available in the application. The learning models include batuter (storytelling), maca ke nulis (reading and writing), aksara, lawas (poetry), balawas (rhyming), basakeco (developing poetry), speeches and writing short stories in Samawa or Sumbawa language. All Sumbawa language materials are available in the application which is also equipped with learning videos. To be able to access the material presented, users must first register and then be able to take part in learning, quizzes and post-tests. After the testing process was carried out on the application using black box testing on three actors, namely the Dikbud admin, teachers and students, it was stated that all application functionality in the twelve tables could function properly.